Study of caesarean section at tertiary care centre: a retrospective study - Kose, Varsha; Sadhvi, Kumari (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Caesarean section (C-section) is one of the most widely performed surgical procedure in obstetrics worldwide. The WHO guidelines revised in 1994 states that the proportion of C-section birth should range between 5-15% but both in developed and developing countries C-section rate is on the rise. This study was conducted to analyse the frequency and indications for C-section and associated maternal morbidity and mortality. Methods: This retrospective study was conducted over a period from January 2018 to May 2019 at the department of obstetrics and gynecology, NKP Salve Institute of Medical Sciences and Research Centre and Lata Mangeshkar Hospital, Hingna, Nagpur, Maharashtra, India. Data of patients who delivered by C-section in our hospital during the defined study period were studied and statistically analysed according to various parameters namely, the frequency of caesarean section, its indications, age, parity and gestational age of the patient. Results: The total number of women delivered over the study period were 2811. Out of which C-sections were done in 1461 women (51.97%). Previous C-section was the leading indication in 35.72% women followed by fetal distress 14.09%, failure of induction 12.93%, arrest of labour 7.93%, PIH 7.18%, oligo/IUGR 6.50%, breech 4.44%, refusal of vaginal birth 4.24%, CPD 1.71%, bad obstetrics history (BOH) 1.43%, malpresentation 1.30%, prematurity 1.23%, and multifetal gestation in 1.09% women. Two women had classical C-section 0.07. 14.09% women had various complications. There was no maternal mortality. Conclusions: A high rate of caesarean deliveries was observed. Individualization of the indication and careful evaluation, following standardized guidelines can help us to limit C-section. Audit and feedback are the best way to judge clinical practice and to reduce the frequency of caesarean section in any tertiary setup.